Diseño de una máquina tendedora de tela jeans para la microempresa textil The Fralex. - Gavilema Orozco, Christian Jonathan (2021)
The micro business sectors of the Pelileo canton of the province of Tungurahua dedicated to textile production do not have adequate technology within their production processes. This has as a result several factors that affect the decrease in efficiency in the textile process such as: minimization of the final quality of the work, increase in the times of the productive processes in the manufacture of garments, increase in the cost of the product due to labor, since the fabric laying operations are carried out manually, which generates errors of more or less two centimeters compared to the main line, which for the company represents a loss due to the large number of folds that are made in each cut, regardless of the type of fabric used. The design of the project is highly feasible since many people who are dedicated to textile production and want to reduce the waste of raw material generated by inaccurate folding and therefore increase the number of garments in each cut.